Rapid fabrication of microfluidic chips based on the simplest LED lithography. (17th April 2015) - Li, Yue; Wu, Ping; Luo, Zhaofeng; Ren, Yuxuan; Liao, Meixiang; Feng, Lili; Li, Yuting; He, Liqun
Abstract: Microfluidic chips are generally fabricated by a soft lithography method employing commercial lithography equipment. These heavy machines require a critical room environment and high lamp power, and the cost remains too high for most normal laboratories. Here we present a novel microfluidics fabrication method utilizing a portable ultraviolet (UV) LED as an alternative UV source for photolithography. With this approach, we can repeat several common microchannels as do these conventional commercial exposure machines, and both the verticality of the channel sidewall and lithography resolution are proved to be acceptable. Further microfluidics applications such as mixing, blood typing and microdroplet generation are implemented to validate the practicability of the chips. This simple but innovative method decreases the cost and requirement of chip fabrication dramatically and may be more popular with ordinary laboratories.